Aptamer functionalized multifunctional fluorescent nanotheranostic platform for pancreatic cancer - Nigam, Preeti; Waghmode, Shobha A.; Yeware, Amar M.; Nawale, Laxman U.; Dagde, Priyanka; Dudhane, Amol; Sarkar, Dhiman (Journal of Nanopharm Drug Delivery, 2014)
This study explores the potential of aptamer functionalized and fluorescent silver nanoparticles (AgNPs) labeled human serum albumin nanoparticles for drug delivery and bioimaging. Nanotechnology is certainly the most promising research arena in recent years and different fields of biotechnology, medicine and agricultural have been deeply benefited by the enormous advantages of nanotechnology. In recent years, synthesis of nanoparticles via eco-friendly methods has attained a lot of interest and silver nanoparticles are synthesized extensively due to their size tunable properties and vast applicability in different areas. In this study we have explored green synthesized fluorescent silver nanoparticles as a novel bioimaging agent for pancreatic cancer. Capsaicin, a plant phytochemical found in red chilli pepper was encapsulated in aptamer MUC-1 coupled albumin nanoparticles and it was observed that the nanoformulation significantly enhanced the bioavailability and sustained release property of the drug to pancreatic cancer cells in-vitro. Meanwhile AgNPs mediated excellent bioimaging has enhanced the efficacy of our system as drug delivery vehicle.

GSH Induced controlled release of levofloxacin from a purpose-built prodrug: luminescence response for probing the drug release in escherichia coli and staphylococcus aureus - Pal, Suman; Ramu, Vadde; Taye, Nandaraj; Mogare, Devraj G.; Yeware, Amar M.; Sarkar, Dhiman; Reddy, D. Srinivasa; Chattopadhyay, Samit; Das, Amitava (Bioconjugate Chemistry, 2016)
Fluoroquinolones are third-generation broad spectrum bactericidal antibiotics and work against both Gram-positive and Gram-negative bacteria. Levofloxacin (L), a fluoroquinolone, is widely used in anti-infective chemotherapy and treatment of urinary tract infection and pneumonia. The main pathogen for urinary tract infections is Escherichia colt, and Streptococcus pneumoniae is responsible for pneumonia, predominantly a lower respiratory tract infection. Poor permeability of L leads to the use of higher dose of this drug and excess drug in the outer cellular fluid leads to central nervous system (CNS) abnormality. One way to counter this is to improve the lipophilicity of the drug molecule, and accordingly, we have synthesized two new Levofloxacin derivatives, which participated in the spatiotemporal release of drug via disulfide bond cleavage induced by glutathione (GSH). Recent studies with Streptococcus mutants suggest that it is localized in epithelial lining fluid (ELF) of the normal lower respiratory tract and the effective [GSH] in ELF is similar to 430 mu M. E. coli typically cause urinary tract infections and the concentration of GSH in porcine bladder epithelium is reported as 0.6 mM for a healthy human. Thus, for the present study we have chosen two important bacteria (Gram + ve and Gram - ve), which are operational in regions having high extracellular GSH concentration. Interestingly, this supports our design of new lipophilic Levofloxacin based prodrugs, which released effective drug on reaction with GSH. Higher lipophilicity favored improved uptake of the prodrugs. Site specific release of the drug (L) could be achieved following a glutathione mediated biochemical transformation process through cleavage of a disulfide bond of these purpose-built prodrugs. Further, appropriate design helped us to demonstrate that it is possible also to control the kinetics of the drug release from respective prodrugs. Associated luminescence enhancement helps in probing the release of the drug from the prodrug in bacteria and helps in elucidating the mechanistic pathway of the transformation. Such an example is scarce in the contemporary literature.

Superoxide generation and its involvement in the growth of mycobacterium smegmatis - Yeware, Amar M.; Shurpali, Ketaki D.; Athalye, Meghana C.; Sarkar, Dhiman (Frontiers in Microbiology, 2017)
Superoxide generation is inevitable in aerobic organisms, most of which have developed mechanisms to detoxify superoxides. However, its significance has not been clearly understood in mycobacteria. This study demonstrates that NADH oxidase is the major source of superoxide in Mycobacterium smegmatis and elucidates the involvement of superoxide in M. smegmatis growth. The maximum inhibition of superoxide generation was observed in the presence of diphenyleneiodonium chloride (DPI), an NADH oxidase inhibitor, compared to other standard inhibitors. After incubation for 24 h, the number of colony forming units (CFUs) was reduced by 6.8 log10 compared to the untreated culture. The inhibitory effect of DPI on M. smegmatis was reversed when the same culture was supplemented with menadione and pyrogallol, which are superoxide generators. Thus, this study reports the source of superoxide generation and its involvement in the growth of M. smegmatis.

Antibacterial and anti-TB tat-peptidomimetics with improved efficacy and half-life - Bhosle, Govind S.; Nawale, Laxman; Yeware, Amar M.; Sarkar, Dhiman; Fernandes, Moneesha (European Journal of Medicinal Chemistry, 2018)
Non-natural antimicrobial peptides are ideal as next-generation antibiotics because of their ability to circumvent the problems of drug resistance and in vivo instability. We report novel all-alpha- and alpha,gamma-mixed Tat peptide analogues as potential antibacterial and anti-TB agents. These peptides have broad spectrum antibacterial activities against Gram-positive (MICs 0.61 +/- 0.03 to 1.35 +/- 0.21 mu M with the peptide gamma TatM4) and Gram-negative (MICs 0.71 +/- 0.005 to 1.26 +/- 0.02 M with gamma TatM4) bacteria and are also effective against active and dormant forms of Mycobacterium tuberculosis, including strains that are resistant to rifampicin and isoniazid. The introduction of the non-natural amino acids of the study in the Tat peptide analogues results in increased resistance to degradation by proteolysis, significantly increasing their half-life. The peptides appear to inhibit bacteria by a membrane disruption mechanism, and have only a low cytotoxic effect on mammalian cells. (C) 2018 Elsevier Masson SAS. All rights reserved.